Primary breast angiosarcoma: A case report - He, Yu; Qian, Liyuan; Chen, Lang; Liu, Yang; Wen, Yanguang; Cao, Peiguo (Frontiers in Surgery, 2023)
Background Primary breast angiosarcoma is a rare sarcoma, accounting for only 0.04% of all breast malignancies, with a difficult diagnosis and a poor prognosis. Mastectomy is the standard treatment, and the role of adjuvant treatment (chemotherapy and/or radiotherapy following surgery) remains uncertain with very few studies. Case Presentation We report a case of a 17- year-old female patient who presented with a right breast lump that had rapidly increased in size and was hemorrhaging. She was diagnosed with breast angiosarcoma by needle biopsy and pathological evaluation. However, the mass showed a quick inclination to bleeding during biopsies. After that, we performed angiography and tumor vascular embolization. The patient underwent a mastectomy followed by adjuvant chemotherapy. Conclusion Tumor vascular embolization reduced the surgical risk of primary breast angiosarcoma with hemorrhage complication. Postoperative therapeutic roles still need further exploration and verification.